2005
DOI: 10.1172/jci25694
|View full text |Cite
|
Sign up to set email alerts
|

Payment of clinical research subjects

Abstract: Offering payment to clinical research subjects, in an effort to enhance recruitment by providing an incentive to take part or enabling subjects to participate without financial sacrifice, is a common yet uneven and contentious practice in the US. Concern exists regarding the potential for payment to unduly influence participation and thus obscure risks, impair judgment, or encourage misrepresentation. Heightening these concerns is the participation not only of adults but also of children in pediatric research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
343
1
15

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 292 publications
(363 citation statements)
references
References 36 publications
4
343
1
15
Order By: Relevance
“…Some authors have raised concerns that payments to underserved populations represents coercion, while others have suggested that payments may bias study results obtained or population recruited. [73][74][75][76][77][78][79] Accordingly, payments could potentially have a negative impact on trust, especially in vulnerable populations that might already be distrustful of research.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have raised concerns that payments to underserved populations represents coercion, while others have suggested that payments may bias study results obtained or population recruited. [73][74][75][76][77][78][79] Accordingly, payments could potentially have a negative impact on trust, especially in vulnerable populations that might already be distrustful of research.…”
Section: Discussionmentioning
confidence: 99%
“…40,62,69 Controversy and contention still exist internationally concerning the ethics of monetary compensation to parents and investigators. 40,70 However, findings from this literature review showed that there are poorer governance structures and greater concerns regarding inducement or coercion in LMICs. More empirical work is needed to guide appropriate and ethical distribution of research benefits in LMICs.…”
Section: Conducting Trials In Children Inmentioning
confidence: 80%
“…The lack of animal models that can reliably predict vaccine efficacy means that development still unavoidably relies on testing of novel vaccines in healthy individuals. Given the often unquantifiable risks to the recipients of vaccines in early stages of development, clinical trials have traditionally relied on informed and consenting volunteers who appreciate the potential risks but still choose to participate for altruistic reasons [6,7]. But relying on altruism alone to facilitate clinical trials is potentially unsustainable and ethically contentious.…”
mentioning
confidence: 99%
“…To date, the relatively meagre compensation that participants often receive could be seen to belittle and undervalue the contribution of these individuals to global health. The modest financial remuneration commonly provided often means that students and the unemployed make up the bulk of volunteers [6,8,9]. As a result, the risks of developing a health intervention that would benefit the whole population are carried disproportionately by some of society's most poor and vulnerable.…”
mentioning
confidence: 99%
See 1 more Smart Citation